Strategi Pengembangan Kawasan Peternakan Sapi Potong Berbasis Sumberdaya Lokal di Kabupaten Solok Selatan - S. Octarini; J. Hellyward; F. Madarisa (Universitas Batanghari Jambi, 2022)
This study aims to analyze the potential, carrying capacity of local resources and strategies for developing beef cattle farming areas. This research was conducted in seven sub-districts in South Solok Regency on the basis of this area as a local cattle center in West Sumatra and the flagship program